Mass spectrometry and theoretical calculations about the loss of methyl radical from methoxilated coumarins - Borkowski, Eduardo Jorge (2015)
In this study we have performed CID mass spectrometry measurements and theoretical calculations in a selected series of coumarins. Our theoretical and experimental results indicate that there is room for reasonable doubts about the fragmentation way previously proposed by Shapiro and Djerassi (1965). A complementary explanation about the fragmentation way of the methyl loss from methoxy coumarins has been reported in this work. Our results demonstrated that different theoretical models are very useful to explain the fragmentation occurred in MS, supporting the usual rules of fragmentation. Although the QTAIM analysis gives a good correlation in order to explain the formation of p-quinoid resonance forms; however, the best correlation has been obtained using the NBO approximation as well as from the Wiberg indexes.